Denmark : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
The paper discusses the flexicurity model, its key policy elements, and association with a low unemployment rate and a high standard of social security for the unemployed. It provides details of an empirical analysis of unemployment performance and the flexicurity model. It also presents selected stylized facts about Danish housing price developments and focuses on tax treatment affecting the market. It also shows an empirical result on developments in the housing finance market and in the Danish taxation of housing.